Perkuatan Fondasi Telapak Dengan Turap - Sumiyanto Sumiyanto; Paulus Setyo Nugroho (Dinamika Rekayasa, 2009)
Reinforcement Foundation is a method to increase the capacity of supporters, so they can support the load of the building. This is required for buildings located on soft ground. Strengthening this foundation is also needed if the structure above will be increased so that the burden of building work increased. In this study, attempted to strengthen the foundations of the method by placing the sheet piles on the side of the foundation. Tests performed on two-dimensional model in the laboratory, by comparing the carrying capacity of  the foundation with sheet piles and without sheet piles. Strengthening the foundation carried out with 3 (three) length variation of plaster  that is: L / B = 0.75, L / B = 1.00 and L / B = 1.25. B, and 3 (three) variations in the location of plaster, which is in distance S / B = 0.5, S / B = 1.0 and S / B = 1.5. Test results showed that the installation of sheet piles can increase the capacity of foundation support. The results of this study showed the longer the higher the sheet piles supporting capacity building, with the results of 33%, 55% and (80% -100%), one each for L / B = 0.75; 1.00 and 1.25. However, increased capacity is not much influenced by the location of plaster especially for short plaster of L / B = 0,75 and L / B = 1,00. While for L / B =1,25, where the sheet piles getting close to the foundation, increase capacity increased as well.